Diet and nutritional status among children 24-59 months by seasons in a mountainous area of Northern Vietnam in 2012 - Le Thi Huong; Le Thi Thanh Xuan; Le Hong Phuong; Doan Thi Thu Huyen; Joacim Rocklöv (Taylor & Francis Group, 2014)
Background: Seasonal variation affects food availability. However, it is not clear if it affects dietary intake and nutritional status of children in Vietnam. Objectives: This paper aims at examining the seasonal variation in nutrition status and dietary intake of children aged 24-59 months. Design: A repeated cross-sectional study design was used to collect data of changes in nutritional status and diets of children from 24 to 59 months through four seasons in Chiem Hoa district, Tuyen Quang province, a predominately rural mountainous province of northern Vietnam. The quantitative component includes anthropometric measurements, 24 hours dietary recall and socio-economic characteristics. The qualitative component was conducted through focus group discussions (FGDs) with mothers of the children surveyed in the quantitative component. The purpose of FGDs was to explore the food habits of children during the different seasons and the behaviours of their mothers in relation to the food that they provide during these seasons. Results: The prevalence of underweight among children aged 24-59 months is estimated at around 20-25%; it peaked in summer (24.9%) and reached a low in winter (21.3%). The prevalence of stunting was highest in summer (29.8%) and lowest in winter (22.2%). The prevalence of wasting in children was higher in spring and autumn (14.3%) and lower in summer (9.3%). Energy intake of children was highest in the autumn (1259.3 kcal) and lowest in the summer (996.9 kcal). Most of the energy and the nutrient intakes during the four seasons did not meet the Vietnamese National Institute of Nutrition recommendation. Conclusions: Our study describes some seasonal variation in nutrition status and energy intake among children in a mountainous area northern Vietnam. Our study indicated that the prevalence of stunting and underweight was higher in summer and autumn, while the prevalence of wasting was higher in spring and autumn. Energy intake did not always meet national recommendations, especially in summer.